Iodine intake in Norwegian women and men: The population-based Tromsø Study 2015–2016 - Madar, Ahmed Ali; Heen, Espen Kolstad; Hopstock, Laila Arnesdatter; Carlsen, Monica Hauger; Meyer, Haakon E (Nutrients, 2020)
Ensuring sufficient iodine intake is a public health priority, but we lack knowledge about the status of iodine in a nationally representative population in Norway. We aimed to assess the current iodine status and intake in a Norwegian adult population. In the population-based Tromsø Study 2015–2016, 493 women and men aged 40–69 years collected 24-h urine samples and 450 participants also completed a food frequency questionnaire (FFQ). The 24-h urinary iodine concentration (UIC) was analyzed using the Sandell–Kolthoff reaction on microplates followed by colorimetric measurement. Iodine intake was estimated from the FFQ using a food and nutrient calculation system at the University of Oslo. The mean urine volume in 24 h was 1.74 L. The median daily iodine intake estimated (UIE) from 24-h UIC was 159 µg/day (133 and 174 µg/day in women and men). The median daily iodine intake estimated from FFQ was 281 µg/day (263 and 318 µg/day in women and men, respectively). Iodine intake estimated from 24-h UIC and FFQ were moderately correlated (Spearman rank correlation coefficient r = 0.39, p < 0.01). The consumption of milk and milk products, fish and fish products, and eggs were positively associated with estimated iodine intake from FFQ. In conclusion, this shows that iodine intake estimated from 24-h UIC describes a mildly iodine deficient female population, while the male population is iodine sufficient. Concurrent use of an extensive FFQ describes both sexes as iodine sufficient. Further studies, applying a dietary assessment method validated for estimating iodine intake and repeated individual urine collections, are required to determine the habitual iodine intake in this population.